If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -6)(y + 8) = 0 Reorder the terms: (-6 + X)(y + 8) = 0 Reorder the terms: (-6 + X)(8 + y) = 0 Multiply (-6 + X) * (8 + y) (-6(8 + y) + X(8 + y)) = 0 ((8 * -6 + y * -6) + X(8 + y)) = 0 ((-48 + -6y) + X(8 + y)) = 0 (-48 + -6y + (8 * X + y * X)) = 0 (-48 + -6y + (8X + yX)) = 0 Reorder the terms: (-48 + 8X + -6y + yX) = 0 (-48 + 8X + -6y + yX) = 0 Solving -48 + 8X + -6y + yX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 8X + -6y + 48 + yX = 0 + 48 Reorder the terms: -48 + 48 + 8X + -6y + yX = 0 + 48 Combine like terms: -48 + 48 = 0 0 + 8X + -6y + yX = 0 + 48 8X + -6y + yX = 0 + 48 Combine like terms: 0 + 48 = 48 8X + -6y + yX = 48 Add '6y' to each side of the equation. 8X + -6y + 6y + yX = 48 + 6y Combine like terms: -6y + 6y = 0 8X + 0 + yX = 48 + 6y 8X + yX = 48 + 6y Reorder the terms: -48 + 8X + -6y + yX = 48 + 6y + -48 + -6y Reorder the terms: -48 + 8X + -6y + yX = 48 + -48 + 6y + -6y Combine like terms: 48 + -48 = 0 -48 + 8X + -6y + yX = 0 + 6y + -6y -48 + 8X + -6y + yX = 6y + -6y Combine like terms: 6y + -6y = 0 -48 + 8X + -6y + yX = 0 The solution to this equation could not be determined.
| 4=80-q | | f(x)=-0.06x^3+18x^2+800x-5000 | | 4y^2=50 | | -5+4y=53 | | -1=4(w-4)-7w | | 2x+6-5x=14-14x+11x-8 | | 4m^3-21m-18=0 | | 3+4(2-x)=3x+(-x-7) | | 19z=95 | | X^2+10w-2=0 | | 0.12(18)+0.002X=0.06(12+X) | | 24-4(2-x)=0 | | 150=15g | | y=(2.5)x | | 12t=192 | | -x^2+37=0 | | Lg(x+4)-lg(x+1)=1 | | 525.00+0.21n=585.00+0.13 | | (7x+3)(3x+1)= | | 8m-5m=12 | | -4v=-80 | | (7x)(2xy)= | | 9x-17=7x-11 | | -26+x=x+12 | | 3x+10x=5x-6 | | 8x-19x=-22 | | (x+2)*(x+2)-(x*4)=40 | | 3x+5=2x+1(2) | | 19+c=19 | | 48=a-4+11-5 | | 80-z=69 | | 10+16+7-h=5 |